PERBANDINGAN MODEL PEMBELAJARAN BAMBOO DANCING DAN RTE TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI XI IPA SMAN 9 KOTA JAMBI - Mutia Samrotul Fuadah; Pratiwi Indah Sari (SJEE (Scientific Journals of Economic Education), 2020)
The purpose of this study was to determine the comparison of the application of the learning model, namely the Bamboo Dancing learning model and the RTE learning model in economic subjects with the material of monetary policy and fiscal policy in class XI IPA SMAN 9 Jambi City. Based on the research results, it was obtained the analysis in the control class of the initial pre-test results of 5 students who passed and in the final pre-test as many as 10 students who passed. Meanwhile, in the experimental class the results of the initial pre-test were 14 students who passed and the final pre-test was 18 students who passed. Meanwhile, in the control class post-test there were 24 students who did not reach the KKM (64.86%) and only 13 students who reached the KKM (35.13%), and in the post-test the experimental class students who got scores below the KKM 6 students (16.67%) and above the KKM 30 students (83.33%). Thus, the Bamboo Dancing model can help students to be more focused in learning and participate actively in the process of learning activities. Thus, it makes it easier for students to understand the subject matter delivered by the teacher in teaching and learning activities.